United Arab Emirates (UAE) : Legal Reforms to Strengthen Women’s Economic Inclusion - Case Study - World Bank Group (World Bank, Washington, DC, 2022)
In 2019-2020, the United Arab Emirates (UAE) introduced a historic package of legal reforms aimed at strengthening women’s economic participation, in line with its national policy commitment to gender balance. The reforms signified a major milestone for the region, introducing paid parental leave in the private sector for the first time in the Middle East and North Africa (MENA), enabling women to choose where to live and to travel outside the home and internationally in the same way as men, introducing the principle of equal pay for work of equal value, and lifting the obedience provision in the UAE’s Personal Status Law. This case study explores the nature of the legal reforms in the UAE, their potential implications for women’s economic empowerment and the UAE’s gender policy goals, and the factors that provided the enabling conditions for change.